Development and Evaluation of Ventilator Turbine Prototype as a Source of Renewable Energy for Rural Community Empowerment - Fahmi Ivannuri; Lilik Subiyanto; Anggara Trisna Nugraha (Maritime in Community Service and Empowerment, 2024)
Energy demand in Indonesia, as well as globally, continues to increase. Hydroelectric power plants (HEPP), along with steam power plants (SPP) and gas power plants (GPP), play a crucial role in electricity supply. Indonesia, an archipelagic country located along the equator, is uniquely positioned with abundant wind energy potential. Remote communities, which often face challenges in accessing electricity, could benefit from utilizing this renewable resource. The ventilator turbine, primarily designed for air circulation, is installed on rooftops of residential and industrial buildings to function as ventilation. Previous research has explored the use of ventilator turbines as wind-powered electricity generators, yet several improvements are still needed. This research focuses on enhancing the performance of the ventilator turbine by connecting the wind turbine to a generator through a V-belt system, which maximizes the rotational speed and energy output. The generator then produces electricity that can be utilized by local communities, providing a sustainable and eco-friendly energy solution. This research aims to contribute to community empowerment by introducing renewable energy technologies that can be locally maintained and managed, thus promoting economic independence in rural areas.